Immune Response-Related Genes – STAT4, IL8RA and CCR7 Polymorphisms in Lung Cancer: A Case–Control Study in China - Ma Y; Zhou Y; Zhang H; Su X (Dove Medical Press, 2020)
Yunfan Ma, Yinxi Zhou, Huixin Zhang, Xiaoan Su Department of Thoracic Surgery, General Hospital of Ningxia Medical University, Yinchuan, Ningxia 750004, People’s Republic of ChinaCorrespondence: Yunfan MaDepartment of Thoracic Surgery, General Hospital of Ningxia Medical University, #804 Shengli South Road, Xingqing Region, Yinchuan, Ningxia 750004, People’s Republic of ChinaTel/Fax +86 951-6743244Email mayunfan2020@163.comPurpose: This study aimed to evaluate the associations between immune response-related genes – STAT4, IL8RA and CCR7 polymorphisms and risk of lung cancer.Methods: Seven polymorphisms of STAT4, IL8RA and CCR7 were genotyped in 350 cases and 350 controls using a MassARRAY platform.Results: The STAT4 rs1400656-G and rs7574865-T alleles may decrease the susceptibility to lung cancer (prs1400656= 0.020; prs7574865= 0.014); while IL8RA rs1008562-C and CCR7 rs3136685-T alleles may increase the risk of disease (prs1008562< 0.001; prs3136685= 0.018). The STAT4 rs1400656-GA and rs7574865-GT genotypes were determined as protective genotypes against lung cancer risk (prs1400656= 0.048; prs7574865= 0.042). However, IL8RA rs1008562-CG/GG and CCR7 rs3136685-TT genotypes were significantly associated with an elevated risk of disease (prs1008562< 0.0001; prs3136685= 0.020). Genetic model analysis revealed that STAT4 rs1400656 and rs7574865 were relate to a declining risk of disease under dominant and log-additive models (rs1400656: p dominant = 0.014, p log-additive= 0.016; rs7574865: p dominant = 0.013, p log-additive= 0.013). In contrast, IL8RA rs1008562 exhibited a strong correlation with an elevated risk of lung cancer under all three models (p dominant < 0.0001, p recessive = 0.011, p log-additive< 0.0001). Moreover, CCR7 rs3136685 was correlated with an increased risk of disease under recessive and log-additive models (p recessive = 0.007, p log-additive= 0.019); and CCR7 rs17708087 was also identified as a risk factor in the dominant model (p = 0.038).Conclusion: These results widen the scope of knowledge about the association between STAT4, IL8RA and CCR7 polymorphisms and risk of lung cancer.Keywords: lung cancer, signal transducers and activators of transcription 4, STAT4, interleukin 8-receptor alpha, IL8RA, Chemokine (C-C motif) receptor 7, CCR7, single nucleotide polymorphisms, SNPs